2019
DOI: 10.1007/s00520-019-04807-z
|View full text |Cite
|
Sign up to set email alerts
|

Are cancer helplines effective in supporting caregivers? A systematic review

Abstract: Purpose The aims of this systematic review were to summarize the profile of caregivers accessing cancer helplines, to evaluate caregiver satisfaction with the helpline service, and to review the evidence base of intervention studies testing the efficacy of community-based cancer helplines in improving caregiver health and well-being. Methods Four electronic databases (Medline, CINAHL, PsychINFO, and EMBASE) were systematically searched to identify relevant literature, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…Collaboration between palliative care providers and genetics services might need to be reinforced to facilitate knowledge transfer, appropriate patients and relatives referral, and even genetic testing or DNA collection for storage. Discussing hereditary cancers with families in palliative care might also require a specific approach as patients (Mishra et al, 2010; Baile et al, 2011), and relatives (Heckel et al, 2019) may be already overwhelmed. Development of psychosocial support skills (Hopwood, 2005) and resources (McClellan et al, 2013) adapted to genetic information communication might be needed in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…Collaboration between palliative care providers and genetics services might need to be reinforced to facilitate knowledge transfer, appropriate patients and relatives referral, and even genetic testing or DNA collection for storage. Discussing hereditary cancers with families in palliative care might also require a specific approach as patients (Mishra et al, 2010; Baile et al, 2011), and relatives (Heckel et al, 2019) may be already overwhelmed. Development of psychosocial support skills (Hopwood, 2005) and resources (McClellan et al, 2013) adapted to genetic information communication might be needed in palliative care.…”
Section: Discussionmentioning
confidence: 99%
“…This support model combined various educational approaches, and apart from one single-session nurse intervention (Chambers et al, 2014), it was provided in a series of sessions. The support was provided using telephone (Badger et al, 2013;Badger et al, 2011;Badger et al, 2020;Budin et al, 2008;Chambers et al, 2014;Heckel et al, 2019;Nga Fan et al, 2014), a combination of in person and telephone (Bahrami & Farzi, 2014;Kurtz et al, 2005;Northouse et al, 2007), video (Badger et al, 2013;Budin et al, 2008), a webpage (Badr et al, 2016) or a retreat weekend (Arnaert et al, 2010). In four studies, the support was provided as group sessions (Carlsson & Strang, 1998;Chiquelho et al, 2011;Gjerset et al, 2019;Pahlavanzade et al, 2014), and the remaining provided it as one-to-one.…”
Section: Group-based Trained Mbsr Teacher Partnersmentioning
confidence: 99%
“…In addition, they have reported on interventions supporting family caregivers who care for persons with advanced cancer at home (Ahn et al, 2020) and on interventions aiming to improve the care for persons diagnosed with lung cancer (Kedia et al, 2020). The effectiveness of cancer helplines has also been systematically reviewed (Heckel et al, 2019). Fu et al (2017), Ferrell and Wittenberg (2017), and Applebaum and Breitbart (2013) all reviewed randomised control trials of psychosocial interventions.…”
Section: Introductionmentioning
confidence: 99%
“…We found that chat-based hotlines have only been evaluated in high-income countries and that evaluation designs lacked rigor. Systematic reviews of telephonebased hotlines or helplines in specific health areas have been conducted including hotlines for cancer caregiver support (22), cancer patient support (23) tobacco smoking cessation (24,25) and alcohol use (24). Results from these hotline reviews also found that published evaluations mostly come from high income countries.…”
Section: Discussionmentioning
confidence: 99%
“…These reviews also found that there was limited ability to claim efficacy of the hotlines due to lack of rigor in evaluation designs. The handful of randomized trials that were included in these reviews demonstrated positive findings (22,23).…”
Section: Discussionmentioning
confidence: 99%